DEVELOPING PROFESSIONAL COMPETENCE AND TEACHING SKILLS IN EDUCATORS - Avazova Lobar Buriyevna; Meyliyeva Laziza Bekzodovna (Modern American Journals, 2025)
The professional competence of teachers and the enhancement of pedagogical skills are fundamental to achieving high-quality education. In today's rapidly evolving educational environment, where technological integration and student diversity are increasing, educators must continually adapt and grow. This article provides a comprehensive analysis of the components of professional competence, including pedagogical knowledge, subject mastery, reflective practice, classroom management, communication skills, and ethical standards. It also investigates effective strategies for improving teaching skills, such as lifelong learning, collaborative practices, mentorship programs, digital tool integration, and evidence-based methodologies.Furthermore, the article emphasizes the crucial role of institutional and governmental support in sustaining teacher development. Professional learning communities, structured in-service training, performance evaluations, and policy initiatives contribute significantly to the continuous growth of teaching staff. By nurturing a culture of professional development, educators are empowered to deliver inclusive, innovative, and student-centered instruction. The article concludes with practical recommendations for education policymakers, school administrators, and teacher education institutions to foster sustainable professional competence and pedagogical excellence in the teaching profession.
Keywords: professional competence, teaching skills, educator, development, pedagogical improvement, continuous professional development, teacher training, reflective practice, educational quality, lifelong learning, instructional methods